Improving the transition from pediatric to adult diabetes care: the pediatric care provider's perspective in Quebec, Canada. Issue 1 (30th June 2017) - Nakhla, Meranda; Bell, Lorraine E; Wafa, Sarah; Dasgupta, Kaberi
Abstract : Objectives: The transition from pediatric to adult care is a high-risk period for the emerging adult with diabetes. We aimed to determine adequacy of pediatric transition care structures and explore the pediatric diabetes care provider's perceptions of transition care. Research design and methods: In-depth interviews with pediatric diabetes care providers from 12 diabetes centers in Quebec were conducted. We queried alignment with Got Transition's six core elements of healthcare transition, experiences, and barriers to transition care. Interview transcripts were reviewed for themes. Results: Three centers (25%) reported having any elements of formal and structured transition care preparation and planning. When referrals were within center (n=8), pediatric providers perceived that transition was smoother; information sharing relied heavily on verbal communication rather than documented medical summaries. Barriers included lack of adult providers, less flexibility in adult care scheduling, patient struggles with multiple new adult responsibilities, and insufficient understanding by adult providers of these challenges. There was a perception that the quality of pediatric care was better than adult care. Moving out of the pediatric care geographical region appeared to increase risk for poor follow-up. Patient satisfaction and regular follow-up in adult care were thought to be good measures of transition success. Programs that included overlap between pediatric and adult care were perceived as ideal. Conclusions: Important gaps in transition care practices persist. Efforts should focus on improving education in transition practices for pediatric care providers and establishing formal transition policies and structures at the institutional level.